Analysis of Potential Antihypertensive Drug Interactions in Outpatient Hypertension Patients at Arifin Achmad Hospital, Riau Province - Wardaniati, Isna; Dinata, Lisma Ramadhani; Auliya, Nadya Putri (JURNAL PROTEKSI KESEHATAN, 2025)
Hypertension is a cardiovascular disease that tends to increase every year. If left untreated, it can lead to complications and polypharmacy which is at risk of causing drug interactions, one of the most common DRPs that affect patient therapy outcomes. This study aims to analyze the use of antihypertensive drugs and potential drug interactions of outpatient hypertensive patients at RSUD Arifin Achmad Pekanbaru. This study is a retrospective descriptive study with 351 patien using Stockley Drug Interaction edition 8 literature and drugs.com application. The results showed of hypertensive was 67% female and 33% male. The highest age range was 56-65 years (37%). The most common drug combination was amlodipine and bisoprolol as 63 patients and the most common class of (CCB) (36%). Outpatient hypertension patients who experienced drug interactions were 294 patients (84%) and there were no drug interactions 57 patients (16%). Drug interactions based on severity were major 10%, moderate 70% and minor 20%. Based on the mechanism pharmacodynamic interactions 68%, pharmacokinetic 20% and unknown 12%.